Effects of Smartphone Addiction, Social Media Addiction and Fear of Missing Out on University Students' Phubbing: A Structural Equation Model - Talan, Tarik; Dogan, Yunus; Kalinkara, Yusuf (Taylor & Francis Inc, 2024)
Phubbing is a multidimensional disorder in which many addictions intersect due to the nature of smartphones. Therefore, determining the variables that predict the concept of phubbing, the chronic addiction of the digital age, is expected to provide important insights into this behavior. In this regard, the main purpose of the current research is to examine the impact of smartphone addiction, social media addiction, and fear of missing out (FoMO) on phubbing. Data for the study were collected from 208 students at a state university in Turkey. Randomly selected students were reached by the convenience sampling method. The study was conducted in the spring semester of the academic year 2021-2022. The data collection instruments used were a personal information form, the smartphone addiction scale, the social media scale, the FoMO scale, and the Phubbing scale. The obtained data were analyzed using the structural equation model. The research results show that smartphone addiction and social media addiction influence phubbing. On the other hand, FoMO was found to have no influence on phubbing.
Keywords: Internet Addiction; Turkish Version; Consequences; Usage; Reliability; Validity